THE EFFECT OF REBUKING AND EAR-CLOSING TECHNIQUE ON THE ABILITY TO CONTROL AUDITORY HALLUCINATIONS: A CASE STUDY AT THE BINA LARAS SOCIAL REHABILITATION CENTER - Khusnun Nazwa Arifin; Bagus Dwi Cahyono; Nurul Huda; Ronal Surya A; Apriana Rahmawati; Evy Aristawati (Spectra Clinical Case Reports Journal, 2026)
Schizophrenia is characterized by disturbances in thought processes, emotions, and perceptions. Among its symptoms, auditory hallucinations are the most frequently experienced by individuals with schizophrenia. If not managed appropriately, this condition can impair social functioning and increase the risk of destructive behavior. In addition to pharmacological therapy, non-pharmacological interventions such as rebuking and ear-closing techniques can be applied to help control emerging symptoms. This study aims to describe the implementation of nursing care for patients with schizophrenia experiencing sensory perception disorders, specifically auditory hallucinations, through the application of rebuking and ear-closing techniques. Methods: This study used a case study design involving two patients at UPT Rehabilitasi Sosial Pasuruan. Data were collected through interviews, observations, physical examinations, and documentation. The intervention consisted of rebuking and ear-closing techniques implemented once daily for three consecutive days, with each session lasting approximately 30 minutes. Outcomes were evaluated using indicators based on the Indonesian Nursing Diagnosis Standards (SDKI) and Indonesian Nursing Outcome Standards (SLKI), focusing on hallucination frequency, patients’ responses, and independence in controlling auditory hallucinations. After implementing SP1 (Implementation Strategy 1), the results showed that the intervention reduced the frequency of hallucinations. Quantitatively, the first patient demonstrated a 65% improvement in self-control ability, while the second patient showed a 75% improvement. The application of rebuking and ear-closing techniques showed potential benefits in helping patients control auditory hallucinations.